A coarse-grained polarizable force field for the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate. (28th November 2017) - Zeman, Johannes; Uhlig, Frank; Smiatek, Jens; Holm, Christian
Abstract: We present a coarse-grained polarizable molecular dynamics force field for the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF6 ]). For the treatment of electronic polarizability, we employ the Drude model. Our results show that the new explicitly polarizable force field reproduces important static and dynamic properties such as mass density, enthalpy of vaporization, diffusion coefficients, or electrical conductivity in the relevant temperature range. In situations where an explicit treatment of electronic polarizability might be crucial, we expect the force field to be an improvement over non-polarizable models, while still profiting from the reduction of computational cost due to the coarse-grained representation.